Arabic Language Teachers' Efforts to Overcome Students' Difficulties in Reading Arabic Texts in Class VIII A MTs PPM Al-Ikhlash Lampoko / Upaya Guru Bahasa Arab untuk Mengatasi Kesulitan Siswa dalam Membaca Teks Bahasa Arab di Kelas VIII A MTs PPM Al-Ikhlash Lampoko - Hamzah Hamzah; Basri Mahmud; Nur Afiah; Nur Aysa Pitri (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to describe the difficulties experienced by students in reading Arabic texts and the teacher's efforts to overcome students' difficulties in reading Arabic texts in class VIII A MTs PPM Al-Ikhlash Lampoko, Polewali Mandar. The research method used in this study is qualitative research, the type of which is included in field research. Data collection in the study through interviews with research informants. Then analyzed using three stages, namely: 1) Data reduction, 2) Data presentation, and 3) Data verification and drawing conclusions. The results of this study indicate that: 1) the difficulties often experienced by students in reading Arabic texts vary. The difficulties often experienced by students in class VIII A MTs PPM Al-Ikhlash Lampoko are difficulties in recognizing Arabic letters, difficulties in pronouncing Arabic letters, and difficulties in reading and understanding long reading texts. 2) Teachers' efforts to overcome students' difficulties in reading Arabic texts can include; teachers listen to the contents of the text repeatedly to students before students read it themselves. Before giving reading texts to students, teachers provide vocabulary related to the reading text. And teachers provide reading texts that are relevant to students' daily lives.Penelitian ini bertujuan untuk mendeskripsikan kesulitan yang dialami siswa dalam membaca teks bahasa Arab dan upaya guru untuk mengatasi kesulitan siswa dalam membaca teks bahasa Arab di kelas VIII A MTs PPM Al-Ikhlash Lampoko, Polewali Mandar. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif, yang jenisnya termasuk dalam penelitian lapangan. Pengumpulan data dalam penelitian ini dilakukan melalui wawancara dengan informan penelitian. Kemudian dianalisis menggunakan tiga tahap, yaitu: 1) Reduksi data, 2) Penyajian data, dan 3) Verifikasi data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa: 1) kesulitan yang sering dialami siswa dalam membaca teks bahasa Arab bervariasi. Kesulitan yang sering dialami siswa di kelas VIII A MTs PPM Al-Ikhlash Lampoko adalah kesulitan dalam mengenali huruf Arab, kesulitan dalam melafalkan huruf Arab, dan kesulitan dalam membaca dan memahami teks bacaan yang panjang. 2) Upaya guru untuk mengatasi kesulitan siswa dalam membaca teks bahasa Arab dapat meliputi; guru mendengarkan isi teks berulang kali kepada siswa sebelum siswa membacanya sendiri. Sebelum memberikan teks bacaan kepada siswa, guru memberikan kosakata yang berkaitan dengan teks bacaan. Dan para guru menyediakan teks bacaan yang relevan dengan kehidupan sehari-hari siswa.